Phylogenetic analyses of the harvest mouse, Micromys minutus (Rodentia: Muridae) based on the complete mitogenome sequences. (October 2015) - Jing, Jie; Song, Xuhao; Yan, Chaochao; Lu, Ting; Zhang, Xiuyue; Yue, Bisong
Abstract: Harvest Mouse ( Micromys minutus ) has a very wide range of distribution in Asia and Europe. However, the phylogenetic relationship of M. minutus is still uncertain. In this study, we determined the complete mitochondrial (mt) genome sequences of M. minutus, and used the complete mitochondrial genome sequences constructed the phylogenetic tree of Muroidea. The size of the genome is 16, 232 bp in length and has a base composition of 33.6% A, 29.1% T, 24.8% C, and 12.5% G. The mitogenome structure was similar to that of typical vertebrate and other rodents' mitochondrial genomes, includes 13 protein-coding genes, 2 rRNA genes (12S rRNA and 16S rRNA), 22 tRNA genes, and 1 control region. We suggested a new initiation codon for ND5 (NADH dehydrogenase subunit), which has been never reported in the mitochondrial genome of vertebrate. The ML and BI phylogenetic trees, which based on the combination of the 12 protein-coding genes, supported strongly that the genus Micromys was represent an early offshoot within the Muridae with high support values (BI = 1.00, ML = 100). Highlights: The complete mitochondrial genome sequence of Micromys minutus was determined. We proposed a new start codon for ND5 (NADH dehydrogenase subunit). This study strongly suggested the basal position of Micromys within Muridae.